2018
DOI: 10.1371/journal.pone.0204142
|View full text |Cite
|
Sign up to set email alerts
|

Double burden of malnutrition among children under 5 in poor areas of China

Abstract: ObjectiveThe aim of this study was to investigate the nutritional status and its risk factors among children under 5 years, with special focus on the coexistence of under and over nutrition in population level.MethodsWe enrolled 6,570 children under 5 years among 26 counties in poor areas of China. Prevalences of malnutrition (stunting, underweight, wasting, overweight) were calculated. Overweight was evaluated using two indicators–weight for height Z score (WHZ) and body mass index for age Z score (BAZ), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
4
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 27 publications
2
45
4
2
Order By: Relevance
“…Other studies that have examined DBM among preschool children have predominantly used anthropometric indicators to define both over- and under-nutrition ( 31 , 32 ). At the population level, DBM is often characterized as coexistence of OWOB children or adults and stunted or underweight children ( 33 , 34 ); at the individual level, studies have reported the co-occurrence of OWOB and stunting among children ( 14 ). Other DBM analyses have used anemia as a measure of undernutrition ( 16 ), with the advantage that these data are widely available through Demographic and Health Surveys.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies that have examined DBM among preschool children have predominantly used anthropometric indicators to define both over- and under-nutrition ( 31 , 32 ). At the population level, DBM is often characterized as coexistence of OWOB children or adults and stunted or underweight children ( 33 , 34 ); at the individual level, studies have reported the co-occurrence of OWOB and stunting among children ( 14 ). Other DBM analyses have used anemia as a measure of undernutrition ( 16 ), with the advantage that these data are widely available through Demographic and Health Surveys.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true in poor, rural, and ethnic minority areas in China. The prevalence of malnutrition was 19.2% among children under five years in poor areas of China in 2016 [21]. Over 65% of children aged 12–24 months suffered from vitamin D deficiency in 2003 [22].…”
Section: Introductionmentioning
confidence: 99%
“…The 2014 data of the Chinese National Survey on Students' Constitution and Health (CNSSCH) showed that the prevalence of undernutrition was 10.0% among Han students [2]. Undernutrition prevalence went up to 19.2% among children under five in the poor areas of China, according to the 2016 data from the United Nations International Children's Emergency Fund (UNICEF) and the National Health and Family Planning Commission of China (NHFPC) [3]. On the other hand, the prevalence of both adult and childhood obesity in China has sharply increased in recent years.…”
Section: Introductionmentioning
confidence: 99%